2017
DOI: 10.1186/s13561-017-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Does birth under-registration reduce childhood immunization? Evidence from the Dominican Republic

Abstract: The consequences of lacking birth certificates remain largely unexplored in the economic literature. We intend to fill this knowledge gap studying the effect of lacking birth certificates on immunization of children in the Dominican Republic. This is an interesting country because a significant number of children of Haitian descent face the consequences of lacking proper documentation. We use the distance to the civil registry office and the mother’s document of identification as instrumental variables of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
(24 reference statements)
0
20
1
Order By: Relevance
“…Without the proof of identity linked to birth registration, accessing government social transfers, the banking system and voter registration is challenging or impossible 11. Research also indicates that birth registration can help protect children from abuse and exploitation32 33 and is associated with improved health outcomes, including early childhood growth and development 34–36…”
Section: Introductionmentioning
confidence: 99%
“…Without the proof of identity linked to birth registration, accessing government social transfers, the banking system and voter registration is challenging or impossible 11. Research also indicates that birth registration can help protect children from abuse and exploitation32 33 and is associated with improved health outcomes, including early childhood growth and development 34–36…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that additionally controlling for cluster characteristics did not add explanatory power, thereby minimizing the possibility that these associations are due to community characteristics within clusters within countries. Prior studies have also documented links between birth registration and children’s healthcare utilization, school enrollment and completion, and participation in social services (e.g., cash transfer programs and government food programs) [ 12 – 14 ]. Our findings extend this evidence by demonstrating how such services do, in turn, explain a considerable proportion of the direct associations between birth registration and early child nutrition and development outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…cash transfer schemes) and enrollment in school [ 12 – 17 ]. Without a birth certificate, a child's exact age is challenging to prove, which is important for ensuring that children receive age-appropriate recommended schedule of vaccinations [ 14 ], applying correct growth standards to estimate children's nutritional status (i.e., height-for-age or weight-for-age) [ 18 , 19 ], and verifying that children are at least a minimum age upon entering school. As children grow older, a birth certificate can provide important documentation in protecting against child labor, trafficking, and sexual exploitation [ 1 , 12 ]; all which are associated with poor child health and wellbeing outcomes [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Birth registration has many benefits for individuals, including to provide legal identity for citizenship and voting rights, as a requirement to access social security benefits and health and education services, and, more generally, as a fundamental human right [1][2][3][4]. At a societal level, complete birth registration within a national civil registration and vital statistics (CRVS) system is the best source of fertility statistics which are used to monitor birth rates and family planning programs, calculate early age and maternal mortality indicators, develop population projections and plan government service provision [1].…”
Section: Introductionmentioning
confidence: 99%